Papaya Peel Extract and Citric Acid Addition on the Quality of Guava Jelly - Kosasih, Sofia Winnie; Karo-Karo, Terip; Romauli, Nauas Domu Marihot (Talenta Publisher, 2023)
The aim of this study was to determine the quality of guava jelly after the addition of papaya peel extract and citric acid. The study used a two-factor, randomized factorial design. The first factor was the addition of papaya peel extract (P): (2%;4%;6%;8%), while the second was the addition of citric acid (A): (1%;1,5%;2%;2,5%). The parameters analyzed were moisture content, ash content, total soluble solids, vitamin C content, crude fiber content, degree of acidity (pH), and total acid. According to the results, the addition of papaya peel extract had a highly significant effect on the water content, crude fiber content, degree of acidity, total acid, and had a differ significant effect on ash content and total dissolved solid. The addition of citric acid also had a highly significant effect on the total dissolved solid, the content of Vitamin C, degree of acidity, the organoleptic test of taste, and had a differ significant effect on water content and total acid. The interaction between the addition of papaya peel extract and citric acid had a highly significant effect on the degree of acidity. Guava jelly with 8% papaya peel extract and 2% citric acid had the optimum quality characteristics.